THE IMPACT OF COUNTERFEIT MONEY CIRCULATION ON MONETARY STABILITY AND THE ROLE OF BANK INDONESIA IN HANDLING IT - Widagdo, Chanandika Dafri; Firmansyah, Hery (Awang Long Law Review, 2025)
The circulation of counterfeit money in Indonesia poses a serious threat to monetary stability and public trust in the rupiah. This issue can disrupt the financial system, undermine the credibility of legal tender, and weaken the effectiveness of monetary policy. Bank Indonesia, as the central bank, plays a critical role in maintaining the integrity of the national currency and ensuring a smooth payment system. Counterfeit money not only undermines the currency’s value but also creates challenges for economic growth and stability. This study aims to analyze the impact of counterfeit money circulation on Indonesia’s monetary stability and evaluate the role of Bank Indonesia in mitigating its effects. Using a normative juridical method with a qualitative descriptive approach, the research relies on secondary data obtained through literature reviews, legal instruments, policy reports, and publications from relevant institutions such as Bank Indonesia and law enforcement agencies. The data are analyzed by interpreting legal norms, institutional functions, and strategic efforts concerning monetary stability. The findings indicate that Bank Indonesia has implemented multi-faceted mitigation strategies, including enhancing the security design of the rupiah, improving public financial literacy through campaigns like “Love, Proud, Understand Rupiah,” and strengthening cooperation with law enforcement to address counterfeit money circulation. However, challenges remain, particularly with technological advancements used by counterfeiters and insufficient public awareness. The study concludes that Bank Indonesia’s role must be continuously strengthened, not only in legal and technological measures but also in increasing public engagement to safeguard the rupiah and ensure monetary stability.